Legal Accountability of Hospitals in the Fulfillment of Patient Rights Based on Permenkes Number 6 of 2026 concerning Hospitals - Dian Hotmaida Sinambela; Lisa Fransisca; Narimani Ganjaring HR; Yanti Ratnasari; Agustinus Purnomo Hadi (Journal of Law and Social Politics, 2026)
Background: Hospitals are healthcare institutions required to provide safe, effective, high-quality, and patient-centered services. Following Law Number 17 of 2023 concerning Health, the Indonesian Government issued Minister of Health Regulation Number 6 of 2026 concerning Hospitals (Peraturan Menteri Kesehatan Nomor 6 Tahun 2026 tentang Rumah Sakit) as a legal framework for hospital governance and administration. However, violations of patients’ rights may still occur, creating a need for legal certainty regarding hospital liability. Objective: This study aims to analyze the regulation of patients’ rights and hospital obligations under Minister of Health Regulation Number 6 of 2026 concerning Hospitals and to examine the forms of hospital legal liability in fulfilling patients’ rights. Methods: This normative legal research employs statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. Results: The findings indicate that Minister of Health Regulation Number 6 of 2026 concerning Hospitals requires hospitals to fulfill patients’ rights through standardized healthcare services, the provision of adequate information, protection of patient privacy, patient safety, and access to quality healthcare. Violations may result in administrative, civil, or criminal liability in accordance with applicable laws and regulations. Patient protection may be pursued through complaint mechanisms, mediation, alternative dispute resolution, or litigation. Conclusion: Strengthening supervision, improving hospital regulatory compliance, and optimizing legal protection mechanisms are essential to ensuring the effective fulfillment of patients’ rights.